(untitled) (Canadian Eye Care Today, 2024)
Giant cell arteritis (GCA) is an important cause of irreversible vision loss in the elderly population. For any physician, making this diagnosis can be difficult due to the highly variable clinical presentation of this large-vessel vasculitis. The 1990 American College of Rheumatology (ACR) classification criteria for GCA are frequently used, however, they were developed to classify GCA patients vs those with other forms of vasculitis and are not true diagnostic criteria. Despite the high predilection of GCA for ocular circulations, the original 1990 criteria did not include any signs or symptoms related to vision. The classification criteria were updated by the ACR and European Alliance of Associations for Rheumatology (EULAR) in 2022 with the significant inclusion of “Sudden vision loss” (Table 1).